Distribution range extension and first record of tonkin numbfish Narcine prodorsalis (Bessednov 1966) (Torpediniformes: Narcinidae) an electric ray in Bangladesh waters (Bangladesh Journal of Zoology, 2018)
Three Tonkin numbfish, Narcine prodorsalis were caught off the coast of Bangladesh in April 2018. Amongst these three specimens, one was morphometrically measured, photographed and transported to be persevered and catalogued at the zoological museum in the University of Dhaka. The specimens were morphologically identified using taxonomic keys and DNA samples (fin clips) have been collected for further studies. These specimens represent the first record of Narcine prodorsalis in Bangladesh waters and extend its distribution range. This is the first western most confirmed record of this species from its previously designated range in the western Pacific and Eastern Indian ocean. This contemporary record includes Bay of Bengal within its current distribution range.Bangladesh J. Zool. 46(2): 147-154, 2018